EDUKASI ECOBRIK SEBAGAI UPAYA PENANGGULANGAN SAMPAH PLASTIK DI SEKOLAH DASAR NEGERI 6 MEULABOH, ACEH BARAT - Mai Suriani; Dini Islama; Mira Mauliza Rahmi; Fitria Rahmayanti; Nurul Najmi; Farah Diana (Universitas Mataram, 2022)
Plastic waste is one type of waste that is not easily biodegradable and is not environmentally friendly. Plastic waste is still a major problem for the community that has not been resolved because of the low level of recycling and the lack of proper handling in the community and schools. The purpose of this activity is as an effort to overcome plastic waste in the Meulaboh State 6 Elementary School (SD) in West Aceh by providing education about ecobric practices and creating positive vibes for students to manage plastic waste into something useful. This educational activity is carried out in two stages, namely the preparation (search of information on the location of the activity implementation and coordination with partners) and the implementation stage (socialization and ecobric practices). The training for partners was carried out using lecture methods, interactive discussions and hands-on practice of making ecobricks with students at SD Negeri 6 Meulaboh, Aceh Barat. The output of this activity is to increase the knowledge and skills of elementary school students through ecobric practices to manage plastic waste around their environment into something useful in everyday life. The conclusion of this activity is that ecobric education is able to minimize the impact of plastic waste through creative, educational and sustainable management, as well as raise awareness of protecting the environment by generating positive vibes from an early age to students. Education and training on making ecobricks at SDN 6 Meulaboh was able to reduce plastic waste in the environment by 11.37 kg.